Survey of the Opinions of the Graduated and Practicing Dentists in Bulgaria and Germany on the Topics of Patient Safety and Medical Error - Schiller, Tihomira; Musurlieva, Nina; Dimitrova-Haruil, Mariana (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Patient safety and medical errors are issues that require research and strategies to deal with. The reasons for the occurrence of an adverse event should be sought among the quality of the received training, fatigue, ineffective communication, the culture of accusation, and the lack of an anonymous report register for training purposes. AIM: The aim of the study is to survey and compare the opinion of the dentists in Bulgaria and Germany on topics related to patient safety and medical error. MATERIALS AND METHODS: A survey with an anonymized questionnaire among dentists from randomly selected for the study purposes Regional Associations of settlements in the Republic of Bulgaria and Germany was used. Respondents answered 25 closed-ended questions divided into five panels: Demographic characteristics of the contingent, the role of study and postgraduate qualifications in acquiring knowledge of errors, willingness to share information about mistakes, factors of error, and culture of accusation. The obtained data were entered and processed with the statistical package IBM SPSS Statistics 20.0. The significance level of the null hypothesis is rejected at p < 0.05. RESULTS: The largest relative share of respondents −72.37% ± 2.64%, is women, in the age range 25–35 years −48.60% ± 2.95%, and with work experience of 6–15 years −34.27% ± 2.81%. Statistically significant differences between the contingents were observed in terms of knowledge acquired during the study of the issue of patient safety (p = 0.005), and whether the study provided sufficient preparation to avoid medical error (p = 0.021). Differences were also found in the data from the issues related to the communication with the patient and the recognition of one’s own mistake (p = 0.034) or the mistake of their colleague (p = 0.004), as well as in terms of fatigue such as risk factor for an adverse event (p = 0.000). The exit data showed differences in the opinion of the two samples and on issues related to medical malpractice reporting and the role of professional organizations. CONCLUSIONS: The majority of respondents believe that they were prepared during their training to identify the causes that could lead to medical errors and that the lack of regular breaks during work increases the risk of making a medical error. They would rather share with the patient an incident caused by themselves, but not one, caused by their colleagues. Respondents are of the opinion that the mistakes are not a sign of incompetence and the responsibility for the mistake lies with the dentist. Most respondents believe that an anonymous register of errors would be useful for their practice.